Volume 3: Heat Transfer; Electric Power; Industrial and Cogeneration 2001
DOI: 10.1115/2001-gt-0404
|View full text |Cite
|
Sign up to set email alerts
|

Computational Design and Experimental Evaluation of Using a Leading Edge Fillet on a Gas Turbine Vane

Abstract: With the desire for increased power output for a gas turbine engine comes the continual push to achieve higher turbine inlet temperatures. Higher temperatures result in large thermal and mechanical stresses particularly along the nozzle guide vane. One critical region along a vane is the leading edge-endwall juncture. Based on the assumption that the approaching flow to this juncture is similar to a two-dimensional boundary layer, previous studies have shown that a horseshoe vortex forms. This vortex forms bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…The span-wise and chord-wise extent of the corner separation is reduced, but no fundamental change in the topology is visible. As suggested by measurements such as those of Zamir (1981), transition in the corner region is typically earlier than for an equivalent flat plate boundary layer. Hence in reality, where pollution and surface roughness also play a role, the extent of separation might lie between that predicted by the fully turbulent and the transitional simulation.…”
Section: Appendix B: Assessment Of the Effect Of Boundary Layer Transmentioning
confidence: 75%
See 2 more Smart Citations
“…The span-wise and chord-wise extent of the corner separation is reduced, but no fundamental change in the topology is visible. As suggested by measurements such as those of Zamir (1981), transition in the corner region is typically earlier than for an equivalent flat plate boundary layer. Hence in reality, where pollution and surface roughness also play a role, the extent of separation might lie between that predicted by the fully turbulent and the transitional simulation.…”
Section: Appendix B: Assessment Of the Effect Of Boundary Layer Transmentioning
confidence: 75%
“…Accounting for cross-flow-induced transition shall be referred to the criteriabased model of Arnal and Juillen (1987) or the recent extensions of the γ -Re θ model by Grabe and Krumbein (2014) and Langtry (2015). Measurements such as those of Zamir (1981) further suggest an earlier transition to turbulence within corner boundary layers compared to corresponding flat-plate conditions. Nevertheless, in order to assess the firstorder effects of transition on the results, transitional simulations are conducted for the baseline rotor-nacelle configuration by employing the γ -Re θ model and the envelope method of Drela and Giles (1987).…”
Section: Flow Solver and Numerical Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar fashion, Zess and Thole (2002) applied a leading edge fillet to a turbine vane. The authors ran simulations on multiple fillet geometries and found a fillet 1 6 high and 2 J long was effective at eliminating the horseshoe vortex.…”
Section: Leading Edge Modificationsmentioning
confidence: 99%
“…While these previous studies have made detailed total pressure traverses and the work of Rose, et al [5] included hotwire traverses, Zess and Thole [7] fully-resolved mean and turbulent flow measurements for a juncture fillet they applied to a large-scale model of a nozzle guide vane. They designed their fillet using the same CFD package as that reported in this paper with the goal of mitigating the formation of the horseshoe vortex.…”
Section: Previous Studiesmentioning
confidence: 99%